Epigenetic: A new approach to etiology of infertility (Faculty of Medicine Universitas Indonesia, 2016)
Infertility is a complex disease which could be caused by male and female factors. The etiology from both factors needs further study. There are some approaches to understanding the etiology of infertility, one of them is epigenetic. Epigenetic modifications consist of DNA methylation, histone modifications, and chromatin remodelling. Male and female germinal cells undergo epigenetic modifications dynamically during differentiation into matured sperm and oocyte cells. In a male, the alteration of DNA methylation in spermatogenesis will cause oligo/asthenozoospermia. In addition, the histone methylation, acetylation, or other histone modification may lead sperm lose its ability to fertilize oocyte. Similarly, in a female, the alteration of DNA methylation and histone modification affects oogenesis, created aneuploidy in fertilized oocytes and resulted in embryonic death in the uterus. Alteration of these epigenetic modification patterns will cause infertility, both in male and female.